Geometrical Structure and Interface Dependence of Bias Stress Induced Threshold Voltage Shift in C(60)-Based OFETs - Ahmed, Rizwan (American Chemical Society, 2014)
[Image: see text] The influence of the nature of interface between organic semiconductor and gate dielectric on bias stress electrical stability of n-type C(60)-based organic field effect transistors (OFETs) was studied. The bias stress induced threshold voltage (V(th)) shift was found to depend critically on the OFET device structure: the direction of V(th) shift in top-gate OFETs was opposite to that in bottom-gate OFETs, while the use of the dual-gate OFET structure resulted in just very small variations in V(th). The opposite direction of V(th) shift is attributed to the different nature of interfaces between C(60) semiconductor and Parylene dielectric in these devices. The V(th) shift to more positive voltages upon bias stress in bottom-gate C(60)-OFET was similar to that observed for other n-type semiconductors and rationalized by electron trapping in the dielectric or at the gate dielectric/C(60) interface. The opposite direction of V(th) shift in top-gate C(60)-OFETs is attributed to free radical species created in the course of Parylene deposition on the surface of C(60) during device fabrication, which produce plenty of hole traps. It was also realized that the dual-gate OFETs gives stable characteristics, which are immune to bias stress effects.